Pyogenic liver abscess trends in South Australia. Issue 3 (14th October 2013) - Chang, Angela Christine; Ha, Ngoc Buu; Satyadas, Thomas; Maddern, Guy
Abstract Background Pyogenic liver abscess (PLA) is an uncommon but potentially life‐threatening condition. Due to advances in diagnostic and treatment methods, the mortality rate has reduced in recent decades. The aim of this study was to gather recent data to examine PLA trends in South Australia. Methods The medical records of all patients admitted to The Queen Elizabeth Hospital, South Australia, between November 2000 and November 2009 with a primary or secondary diagnosis of PLA were retrospectively reviewed. Results Thirty‐six patients were identified. Twenty (55.6%) were male and 16 (44.4%) female. The mean patient age was 70.2 years. A single PLA was found in 21 (58.3%) patients and multiple abscesses in 15 (41.7%) patients. Segment 7 of the liver was most commonly affected (10 cases). In 12 patients, multiple organisms were identified. Escherichia coli, Klebsiella pneumonia and Streptococcus species were most commonly identified. All patients received antibiotics and 27 (75%) received additional treatment. Nine patients received open abscess drainage. Fourteen received ultrasound‐guided or computed tomography‐guided percutaneous drainage or aspiration. One patient died as a direct result of a PLA. Discussion Since its first description, the epidemiology of PLA has changed. Patients diagnosed with PLA are now older, the male predominance is less and the organism more likely to originate from the biliary tract. The approach to PLA has also progressed with more accurate imaging and better treatment methods becoming available, which has resulted in a low mortality rate. This series confirms the described trends in South Australia.